A familial case of periodontal Ehlers–Danlos syndrome lacking skin extensibility and joint hypermobility with a missense mutation in C1R. Issue 7 (1st April 2022) - Nakajima, Kimiko; Suzuki, Hisato; Yamamoto, Mayuko; Yamamoto, Tetsuya; Kawai, Tomoko; Nakabayashi, Kazuhiko; Hata, Kenichiro; Kosaki, Kenjiro; Nakajima, Hideki; Sano, Shigetoshi; Kubo, Akiharu
Abstract: Periodontal Ehlers–Danlos syndrome (pEDS) is an autosomal‐dominant disorder first described by Stewart in 1977 that is characterized by severe gingival recession and periodontitis that triggers premature loss of permanent teeth and alveolar bone absorption. It was recently shown that pEDS is caused by a heterozygous missense mutation in C1R or C1S, which encode complement 1 proteases. Here, we report a familial case of pEDS with a novel heterozygous missense mutation, c.674G>C (p.R225P), in C1R (NM_001733.4). The case exhibited pretibial hyperpigmentation and extended periodontitis but neither skin extensibility nor joint hypermobility, suggesting that this mutation will expand the definition of pEDS.